2008
DOI: 10.1002/chem.200800327
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Sensing with Phosphonate Cavitands

Abstract: Phosphonate cavitands are an emerging class of synthetic receptors for supramolecular sensing. The molecular recognition properties of the third-generation tetraphosphonate cavitands toward alcohols and water at the gas-solid interface have been evaluated by means of three complementary techniques and compared to those of the parent mono- and diphosphonate cavitands. The combined use of ESI-MS and X-ray crystallography defined precisely the host-guest association at the interface in terms of type, number, stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 46 publications
2
68
1
Order By: Relevance
“…2A). The affinity of this class of cavitand toward methanol has been previously reported (13), and also in this case the alcohol is stabilized within the cavity by a hydrogen bond with one P¼O group at the upper rim and by two CH-π interactions between two methyl hydrogens of the guest and two aromatic rings of the host (13). The results indicate that methanol is preferred by the cavitand over glycine methyl ester hydrochloride; the latter could be expected to interact through dipolar interactions between the P¼O groups and the positively charged nitrogen atom.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…2A). The affinity of this class of cavitand toward methanol has been previously reported (13), and also in this case the alcohol is stabilized within the cavity by a hydrogen bond with one P¼O group at the upper rim and by two CH-π interactions between two methyl hydrogens of the guest and two aromatic rings of the host (13). The results indicate that methanol is preferred by the cavitand over glycine methyl ester hydrochloride; the latter could be expected to interact through dipolar interactions between the P¼O groups and the positively charged nitrogen atom.…”
Section: Resultsmentioning
confidence: 77%
“…Among them, tetraphosphonate cavitands are outstanding: Their complexation ability spans from positively charged inorganic and organic species (9) to neutral molecules (10). This diverse complexation ability is the result of three interaction modes, which can be activated either individually or in combination by the host according to the guest requirements: (i) multiple ion-dipole interactions between the inward facing P¼O groups and the positively charged guests (11); (ii) single or dual H bonding involving the P¼O groups (11,12); and (iii) CH-π interactions between a methyl group present on the guest and the cavity of the host (13).…”
mentioning
confidence: 99%
“…(2) To clarify the gas-phase properties of complexes formed by phosphonate cavitands, [9] since one of their applications is gas sensing [10]. The earlier reported results have shown that the phosphonate cavitands are capable of selectively forming complexes with alcohols [11][12][13][14] and ammonium ions [7,15,16], which has just recently led to application of phosphonate cavitands in supramolecular polymers [17], molecular recognition on silicon surfaces [18], and product protection in amine methylation reactions [19]. Number and positioning of the P ϭ O groups at the upper rim and their relative orientation with respect to the cavity are the key host parameters in defining the multiple H-bonding interactions involved in the recognition process [16].…”
mentioning
confidence: 99%
“…Phosphonate cavitands are synthetic abiotic receptors (hosts) [39,40,43] with molecular recognition properties that have been exploited in gas sensing [44], supramolecular polymers [45,46], surface self-assembly [47], and product protection [48]. They are specifically designed to target small molecules bearing amino-functionalities via a synergistic combination of weak interactions such as H-bonding, dipole−dipole, and CH−π interactions.…”
Section: Breaking Good Probing Designer Drug Family With a Unique Sumentioning
confidence: 99%